PEMBERDAYAAN DAN OPTIMALISASI PEMBERIAN ASI BAGI PEDAGANG PASAR TRADISIONAL DAN IBU PEKERJA INFORMAL DI KECAMATAN DELI TUA TAHUN 2024 - Krisna, Putri; Ariani, Peny; ., Fitriani; Sari, Ria Novita; Sari, Mediana (INSTITUT KESEHATAN DELI HUSADA, 2024)
Exclusive breastfeeding is one of the indicators of the success of feeding babies aged 0-6 months which is the basis for providing nutrition in the first 1000 years of life. Most provinces still have a percentage of exclusive breastfeeding below the national average, including North Sumatra at 57,83% (BPS, 2021). The conditionof traditional markets in Indonesia, especially in North Sumatra, is very risky for the health of babies during the breastfeeding process (BPS, 2020).To overcome the obstacles and problems during breastfeeding that have been reported, it can be strengthened by carrying out empowerment which aims to obtain sufficient knowledge and skills for traders who breastfeed, comprehensive support such as providing breastfeeding facilitation, as well as guarantees regarding the right quality and quantity of breast milk.